You are on page 1of 4

# Algebra Cheat Sheet

## Basic Properties & Facts

Arithmetic Operations Properties of Inequalities
b ab If a < b then a + c < b + c and a - c < b - c
ab + ac = a ( b + c ) a =
c c a b
If a < b and c > 0 then ac < bc and <
a c c
a a ac a b
b = = If a < b and c < 0 then ac > bc and >
c bc b b c c

c
Properties of Absolute Value
a c ad + bc a c ad - bc a if a 0
+ = - = a =
b d bd b d bd -a if a < 0
a -b b-a a+b a b a 0 -a = a
= = +
c-d d -c c c c a a
ab = a b =
a b b
ab + ac ad
= b + c, a 0 b = a+b a + b Triangle Inequality
a c bc

d Distance Formula
Exponent Properties If P1 = ( x1 , y1 ) and P2 = ( x2 , y2 ) are two
an 1
a n a m = a n+m m
= a n-m = m-n points the distance between them is
a a
(a )n m
= a nm a 0 = 1, a 0 d ( P1 , P2 ) = ( x2 - x1 ) + ( y2 - y1 )
2 2

n n
a a
( ab )
n
= a nb n = n Complex Numbers
b b
1 1
a -n = -n
= an i = -1 i 2 = -1 -a = i a , a 0
an a
-n n ( a + bi ) + ( c + di ) = a + c + ( b + d ) i
a b bn
( ) = (a )
n 1 n 1

= = n a = a n m
( a + bi ) - ( c + di ) = a - c + ( b - d ) i
m m

b a a
( a + bi )( c + di ) = ac - bd + ( ad + bc ) i
Properties of Radicals
( a + bi )( a - bi ) = a 2 + b 2
1
n
a = an n
ab = n a n b a + bi = a 2 + b 2 Complex Modulus
m n
a = nm a n
a na
= ( a + bi ) = a - bi Complex Conjugate
b nb
( a + bi )( a + bi ) = a + bi
2

n
a n = a, if n is odd
n
a n = a , if n is even

For a complete set of online Algebra notes visit http://tutorial.math.lamar.edu. 2005 Paul Dawkins
Logarithms and Log Properties
Definition Logarithm Properties
y = log b x is equivalent to x = b y log b b = 1 log b 1 = 0
log b b x = x b logb x = x
Example
log b ( x r ) = r log b x
log 5 125 = 3 because 53 = 125
log b ( xy ) = log b x + log b y
Special Logarithms x
ln x = log e x natural log log b = log b x - log b y
y
log x = log10 x common log
where e = 2.718281828K The domain of log b x is x > 0
Factoring and Solving
Factoring Formulas Quadratic Formula
x 2 - a 2 = ( x + a )( x - a ) Solve ax 2 + bx + c = 0 , a 0
x 2 + 2ax + a 2 = ( x + a )
2 -b b 2 - 4ac
x=
2a
x 2 - 2ax + a 2 = ( x - a )
2
If b - 4ac > 0 - Two real unequal solns.
2

## x 2 + ( a + b ) x + ab = ( x + a )( x + b ) If b 2 - 4ac = 0 - Repeated real solution.

x3 + 3ax 2 + 3a 2 x + a 3 = ( x + a )
3 If b 2 - 4ac < 0 - Two complex solutions.

x3 - 3ax 2 + 3a 2 x - a 3 = ( x - a )
3
Square Root Property
x3 + a3 = ( x + a ) ( x 2 - ax + a 2 ) If x 2 = p then x = p

## x3 - a 3 = ( x - a ) ( x 2 + ax + a 2 ) Absolute Value Equations/Inequalities

x -a
2n 2n
= (x -a
n n
)( x n
+a n
) If b is a positive number
p =b p = -b or p = b
If n is odd then,
x n - a n = ( x - a ) ( x n -1 + ax n - 2 + L + a n -1 ) p <b -b < p < b
p >b p < -b or p>b
xn + a n
= ( x + a ) ( x n -1 - ax n - 2 + a 2 x n -3 - L + a n -1 )
Completing the Square
Solve 2 x - 6 x - 10 = 0
2 (4) Factor the left side
2
3 29
(1) Divide by the coefficient of the x 2 x- =
2 4
x 2 - 3x - 5 = 0 (5) Use Square Root Property
(2) Move the constant to the other side.
3 29 29
x 2 - 3x = 5 x- = =
2 4 2
(3) Take half the coefficient of x, square
it and add it to both sides (6) Solve for x
2 2 3 29
3 3 9 29 x=
x 2 - 3x + - = 5 + - = 5 + = 2 2
2 2 4 4

For a complete set of online Algebra notes visit http://tutorial.math.lamar.edu. 2005 Paul Dawkins
Functions and Graphs
Constant Function Parabola/Quadratic Function
y = a or f ( x ) = a x = ay 2 + by + c g ( y ) = ay 2 + by + c
Graph is a horizontal line passing
through the point ( 0, a ) . The graph is a parabola that opens right
if a > 0 or left if a < 0 and has a vertex
Line/Linear Function b b
at g - , - .
y = mx + b or f ( x ) = mx + b 2a 2 a
Graph is a line with point ( 0, b ) and
Circle
slope m.
( x - h) + ( y - k ) = r 2
2 2

## Slope Graph is a circle with radius r and center

Slope of the line containing the two ( h, k ) .
points ( x1 , y1 ) and ( x2 , y2 ) is
y2 - y1 rise Ellipse
m= =
( x - h) ( y -k)
2 2
x2 - x1 run
+ =1
Slope intercept form a2 b2
The equation of the line with slope m Graph is an ellipse with center ( h, k )
and y-intercept ( 0,b ) is with vertices a units right/left from the
y = mx + b center and vertices b units up/down from
Point Slope form the center.
The equation of the line with slope m
and passing through the point ( x1 , y1 ) is Hyperbola
( x - h) ( y -k)
2 2
y = y1 + m ( x - x1 ) - =1
a2 b2
Graph is a hyperbola that opens left and
Parabola/Quadratic Function
right, has a center at ( h, k ) , vertices a
y = a ( x - h) + k f ( x) = a ( x - h) + k
2 2

## units left/right of center and asymptotes

b
The graph is a parabola that opens up if that pass through center with slope .
a > 0 or down if a < 0 and has a vertex a
Hyperbola
at ( h, k ) .
(y -k) ( x - h)
2 2

- =1
Parabola/Quadratic Function b2 a2
y = ax 2 + bx + c f ( x ) = ax 2 + bx + c Graph is a hyperbola that opens up and
down, has a center at ( h, k ) , vertices b
The graph is a parabola that opens up if units up/down from the center and
a > 0 or down if a < 0 and has a vertex asymptotes that pass through center with
b b
b slope .
at - , f - . a
2a 2 a

For a complete set of online Algebra notes visit http://tutorial.math.lamar.edu. 2005 Paul Dawkins
Common Algebraic Errors
Error Reason/Correct/Justification/Example
2 2
0 and 2 Division by zero is undefined!
0 0
( -3 )
2
-32 9 -32 = -9 , = 9 Watch parenthesis!

(x )
2 3
x5 (x )
2 3
= x2 x2 x2 = x6
a a a 1 1 1 1
+ = + =2
b+c b c 2 1+1 1 1
1 A more complex version of the previous
x -2 + x -3
x +x
2 3 error.
a + bx a bx bx
a + bx = + = 1+
1 + bx a a a a
a
Beware of incorrect canceling!
- a ( x - 1) = - ax + a
- a ( x - 1) - ax - a
Make sure you distribute the -!
( x + a) ( x + a) = ( x + a )( x + a ) = x 2 + 2ax + a 2
2 2
x2 + a2
x2 + a2 x + a 5 = 25 = 32 + 42 32 + 42 = 3 + 4 = 7
x+a x + a See previous error.
More general versions of previous three
( x + a)
n
x n + a n and n
x+a n x + n a
errors.
2 ( x + 1) = 2 ( x 2 + 2 x + 1) = 2 x 2 + 4 x + 2
2

2 ( x + 1) ( 2 x + 2 )
2 2
( 2 x + 2)
2
= 4 x2 + 8x + 4
Square first then distribute!
See the previous example. You can not
( 2 x + 2) 2 ( x + 1)
2 2
factor out a constant if there is a power on
the parenthesis!
1
- x2 + a2 = ( - x2 + a 2 ) 2
- x2 + a2 - x2 + a2
Now see the previous error.
a
a ab
a 1 a c ac
b c = = =
b b 1 b b
c
c c
a a
a
ac b = b = a 1 = a
b
c c b c bc
c b
1

For a complete set of online Algebra notes visit http://tutorial.math.lamar.edu. 2005 Paul Dawkins